2011
DOI: 10.1590/s0100-40422011000700009
|View full text |Cite
|
Sign up to set email alerts
|

Síntese e caracterização de argilas organofílicas contendo diferentes teores do surfactante catiônico brometo de hexadeciltrimetilamônio

Abstract: Recebido em 26/8/10; aceito em 16/2/11; publicado na web em 15/4/11 SYNTHESIS AND CHARACTERIZATION OF ORGANOCLAYS USING DIFFERENTS CONTENTS OF CATIONIC SURFACTANT HEXADECYLTRIMETHYLAMMONIUM BROMIDE. The major applications of organoclays are in adsorption of organic polluents. The objective of this work was the synthesis and characterization of organoclays using differents amounts of cationic surfactant hexadecyltrimethylammonium bromide. The clays were characterized by low angle x-ray diffraction (XRD), scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
8
0
3
Order By: Relevance
“…The clay mineral used in this study is expansive, thus allowing the interlamellar distance to be increased, depending on the size of the molecule used for modification. 58 This expansion is measured by the shift of the d 001 diffraction angle, since according to Bragg's law, this angle is inversely proportional to the interatomic distance. A reduction of this angle indicates interlamellar expansion of the clay mineral.…”
Section: Effect Of Ctab Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The clay mineral used in this study is expansive, thus allowing the interlamellar distance to be increased, depending on the size of the molecule used for modification. 58 This expansion is measured by the shift of the d 001 diffraction angle, since according to Bragg's law, this angle is inversely proportional to the interatomic distance. A reduction of this angle indicates interlamellar expansion of the clay mineral.…”
Section: Effect Of Ctab Concentrationmentioning
confidence: 99%
“…The surface area value of 27.8 m 2 g -1 found for the natural clay is considered low, but this is a characteristic of smectite clays and is in line with the values reported in the literature. 16,58,71 The organophilization reduced the surface area, due to the aggregation of the quaternary ammonium salts, which prevents the entrance of nitrogen molecules. The results of other studies indicate this tendency is observed most of the time, although the specific surface area of clay can increase after modification.…”
Section: Specific Surface Area and Average Pore Diametermentioning
confidence: 99%
“…The properties associated with some inorganic solids having organic guest molecules incorporated on the established inorganic layer through immobilization processes leads to new organofunctionalized compounds, which have attracted great attention from both scientific and practical viewpoints [1][2][3][4] . In this context, the grafting involves organosilanes that enable covalent bond formations with available reactive surface groups.…”
Section: Introductionmentioning
confidence: 99%
“…The band located at 3400 cm -1 is characteristic of the water (H-O-H) stretching from interlayer (Araújo et al, 2006;Maia et al, 2019). At 2858 and 2935 cm -1 , bands symmetrical and asymmetric referring to the CH2 groups of the carbon chain of the surfactant adsorbed on the clay are observed (Lopes et al, 2011). In 1465 and 1718 cm -1 , the presence of vibration due to the presence of the CH3 group is observed.…”
Section: Adsorbent Characterizationmentioning
confidence: 99%